Material stock and environmental burdens of coastal bridge infrastructure in China: A bottom-up life cycle perspective - Huanshan Ning; Zhen Guo; Haibo Feng; Peidong Zhang; Jiawei Shen; Zhiwei Zhang (PLoS ONE, 2026)
China’s rapid expansion of maritime infrastructure has positioned coastal bridges as critical components of national economic and transport strategies. However, their material stock scale, material intensity and long-term environmental impacts remain underexamined. This study presents the first integrated assessment of material stock (MS) and lifecycle environmental burdens associated with China’s coastal bridges, using a bottom-up material flow analysis and ReCiPe 2016 midpoint life cycle assessment (LCA). Results based on 510 coastal bridges show a total in-use material stock of 369.32 million tons, with cable-stayed bridges accounting for 63.9%. Suspension bridges exhibit the highest material intensity (18.78 t/km), primarily due to anchorage systems requiring 12.4 times more crushed stone and 4.7 times more concrete than cable-stayed designs. Life cycle assessment reveals that raw material production contributes 66.6% of total environmental impacts, with steel production alone accounting for 60.9% of global warming potential (GWP) and over 90% of mineral scarcity and human carcinogenicity. Although steel comprises only 13.9% of MS, its unit mass impacts are up to 380 times greater than those of sand and gravel. In addition, hidden flows associated with structural overdesign, anticorrosive coatings, and deferred maintenance shift substantial burdens to upstream phases, contributing 27.8% of GWP and 49.9% of marine ecotoxicity. Mitigation strategies include dynamic LCA frameworks, circular material flows, modular low-carbon construction, bio-based coatings, and alignment with global carbon governance. These findings provide practical guidance for advancing low-carbon, climate-resilient coastal infrastructure in China.